PENGARUH KOMBINASI PENYUNTIKAN hCG DAN EKSTRAK KELENJAR HIPOFISA IKAN MAS TERHADAP DAYA RANGSANG OVULASI DAN KUALITAS TELUR IKAN PANTAU (Rasbora lateristriata Blkr) - Putra, Ridwan Manda (Fakultas Perikanan dan Kelautan Universitas Riau, 2010)
This research aims to understand the effect of dosages combination of mixedhCG and hypophysis extract injection toward ovulation and egg quality of Rasboralateristriata Blkr. There were 5 treatments applied, namely PA= control (1 ml of NaCl 0,65 % /kg body weight), PB = hCG 400 IU/kg body weight + CPE 2 dosages,PC = hCG 600 IU/kg body weight + CPE 2 dosages, PD = hCG 800 IU/kg bodyweight + CPE 2 dosages, PE = hCG 1000 IU/kg body weight + CPE 2 dosages, PF= hCG 1200 IU/kg body weight + CPE 2 dosages. The best result for female fish wasthe combination of hCG 1000 IU/kg body weight + CPE 2 dosages and it shown7.16 laten time; 281 eggs/ ovulation, egg diameter increment 0.267 mm and matureeggs increase 16.67%.